Establishing A Legitimate Indonesia’s Government Electronic Surveillance Regulation: A Comparison with The U.S. Legal Practices - Fatihah, Citra Yuda Nur (UI Scholars Hub, 2021)
Cybersecurity and privacy have now become a matter of increasing concern for citizens, the private sector, and the Indonesian government. The government is currently struggling to combat cyberattacks and data breaches. Indonesia is, in fact, in the early stages of developing a national cybersecurity strategy. The legal framework for cybersecurity in Indonesia is still weak. The one and only legal basis for regulating cybersecurity, privacy, and security, in Indonesia so far is the Electronic Information and Transactions Law No. 11/2008 and its revised version Law No.19/2016. Furthermore, the government through the Indonesian Ministry of Communication and Information has just issued the implementing regulation called the Ministerial Regulation Number 5 of 2020. This Ministerial Regulation has several debatable articles and provisions, such as regarding the registration obligation, the content management and safe harbor concept, as well as the censorship issues, and the access availability to government. This article would like to address and examine whether it's lawful for Indonesian government institutions or law enforcers to request such an access to electronic systems and users’ personal data from the Electronic Systems Operators or internet service providers for surveillance and law enforcement purposes. The article then provides legal steps or procedures as well as legal recommendations that Indonesian government entities must follow before conducting such a legitimate electronic cyber operation. This article will also compare those Indonesia’s digital surveillance practices with the United States legal practices and lesson-learned on government surveillance.